Juridical Analysis of Legal Aid Implementation for Underprivileged Communities: Problems and Challenges - Andhini, Alycia Sandra Dinar (The Indonesian Journal of International Clinical Legal Education, 2021)
Legal Aid is organized to help resolve legal issues faced by Legal Aid Recipients. The birth of Law No. 16 of 2011 concerning Legal Aid provides new hope for the poor to gain access to justice and equality before the law. This writing aims to determine the implementation of the provision of legal aid and the obstacles that influence it in its implementation because sometimes the implementation of Law Number 16 of 2011 concerning Legal Aid in Indonesian Courts is not optimal. This research focuses on the application of legal aid to the poor, the challenges and problems they face. The method used in this research is empirical research. This study found that in the application of legal aid in several regions in Indonesia, the main problem faced in addition to the lack of availability of accredited legal aid institutions, was also the issue of the budget provided by the state. In addition, in terms of the legal culture of the community, the implementation of legal aid is not optimal due to the understanding of the community not to have anything to do with the law so that many cases that should receive legal assistance cannot be accompanied.